2019
DOI: 10.3390/ani9110901
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Nutrient Digestibility, Nitrogen Retention, and Meat Quality in Rabbits Fed Diets Supplemented with Sida hermaphrodita

Abstract: Simple SummaryAlfalfa is an important forage crop in rabbit nutrition. Despite the numerous advantages of alfalfa, efforts have been made to find its potential substitutes. Virginia fanpetals (Sida hermaphrodita), is yet another potential substitute for alfalfa in animal diets. The aim of this study was to evaluate the efficacy of dehydrated Virginia fanpetals meal as a substitute for dehydrated alfalfa meal in rabbit diets. The results of this study indicated that Virginia fanpetals meal can be included in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Rabbits fed with T1 diet showed the highest CP digestbility (71.6%), while those fed with T3 diet showed the lowest (68.5%). Purwin et al (2019) found that the CP digestibility of dehydrated alfalfa meal was 71.8%, which is in line with the current study. With increasing demand on animal protein, rabbit is suitable to be reared because of its high ability to convert forage into meat, low cost of production, and high quality protein meat (Amata & Okorodudu, 2016).…”
Section: Dry Matter and Nutrients Intakessupporting
confidence: 93%
“…Rabbits fed with T1 diet showed the highest CP digestbility (71.6%), while those fed with T3 diet showed the lowest (68.5%). Purwin et al (2019) found that the CP digestibility of dehydrated alfalfa meal was 71.8%, which is in line with the current study. With increasing demand on animal protein, rabbit is suitable to be reared because of its high ability to convert forage into meat, low cost of production, and high quality protein meat (Amata & Okorodudu, 2016).…”
Section: Dry Matter and Nutrients Intakessupporting
confidence: 93%
“…Several authors described the fodder nutritional content of S. hermaphrodita and its similarity to alfalfa (Medicago sativa L.) (Borkowska and Styk, 2006, cited in [7], [158]). Fijałkowska et al [159] also studied the silage produced from S. hermaphrodita after harvesting at the bud formation stage, in early-mid June, identifying that the species had a similar chemical constitution to alfalfa, as well as favourable protein and carbohydrate contents for cattle feed.…”
Section: Forage and Fibrementioning
confidence: 99%
“…The industrial use of S. hermaphrodita is mainly in the production of pulp and paper [ 4 ]. It can be used also in soil phytoremediation and detoxification [ 5 , 6 ] and has been tested as a possible substitute of other ingredients in livestock feed mixtures as well [ 7 ]. S. hermaphrodita contains a high amount of sugar in its secreted nectar, which allows the production of 110–315 kg of honey per hectare [ 8 ].…”
Section: Introductionmentioning
confidence: 99%